Restricted accessed nanoparticles for direct magnetic solid phase extraction of trace metal ions from human fluids followed by inductively coupled plasma mass spectrometry detection1. Issue 12 (21st June 2015) - Yan, Ping; He, Man; Chen, Beibei; Hu, Bin
<x xml:space="preserve">Abstract</x> Restricted accessed magnetic nanoparticles were synthesized and applied for direct extraction of trace metals from human fluids.